(untitled) (Third Sector Social Economic Review, 2015)
In this study, analyses which aim to determine the macroeconomic factors that have an impact on the use of currency swap derivatives, which are the most frequently used derivative products in Turkish banking sector, were conducted to understand the dynamics of using derivatives in Turkish banking sector. The relationship between currency swap transactions and macroeconomic variables were analyzed through Granger causality analysis, regression analysis, VAR impulse response analysis and variance decomposition analysis. As a conclusion of these analyses, a relationship between currency swap transactions and off-balance sheet risks, inflation, market risk, Central Bank Reserves and TRY deposits in the banks was found.